The Challenges of Designing and Implementing Clinical Trials With Broccoli Sprouts… and Turning Evidence Into Public Health Action - Fahey, Jed W.; Kensler, Thomas W. (Frontiers in Nutrition, 2021)
Broccoli sprouts are a convenient and rich source of the glucosinolate glucoraphanin, which can generate the chemopreventive agent sulforaphane through the catalytic actions of plant myrosinase or β-thioglucosidases in the gut microflora. Sulforaphane, in turn, is an inducer of cytoprotective enzymes through activation of Nrf2 signaling, and a potent inhibitor of carcinogenesis in multiple murine models. Sulforaphane is also protective in models of diabetes, neurodegenerative disease and other inflammatory processes, likely reflecting additional actions of Nrf2 and interactions with other signaling pathways. Translating this efficacy into the design and implementation of clinical chemoprevention trials, especially food-based trials, faces numerous challenges including the selection of the source, placebo, and dose as well as standardization of the formulation of the intervention material. Unlike in animals, purified sulforaphane has had very limited use in clinical studies. We have conducted a series of clinical studies and randomized clinical trials to evaluate the effects of composition (glucoraphanin-rich [± myrosinase] versus sulforaphane-rich or mixture beverages), formulation (beverage versus tablet) and dose, on the efficacy of these broccoli sprout-based preparations to evaluate safety, pharmacokinetics, pharmacodynamic action and clinical benefit. While the challenges for the evaluation of broccoli spouts in clinical trials are themselves formidable, further hurdles must be overcome to bring this science to public health action.